Methodological adaptation for nematodes extration in forest soils of the southern Mata Atlântica - Moser, Thomas; Frankenbach, Silja (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to clarify whether the method to extract nematodes from European soils is suitable for forest soils and litter in the eastern of Paraná state, Brazil, and whether nematode abundance differs between sites with different ecosystems and levels of human interference. The study sites were situated in the coastal area of the Serra do Mar, near the town of Antonina, in Eastern Paraná, Brazil. Cobb's sieving and decanting method was more appropriate than ISO method, since extraction efficiency was higher and intra-sample variability was significantly lower. In order to achieve an extraction efficiency higher than 90%, Cobb's method was modified. For the extraction of nematodes from litter, the Baermann funnel, with an extraction time of 48 hours, yielded an extraction efficiency higher than 90%. Nematode abundance in litter was higher than in soil. The mean number of individuals extracted from the litter increased with the age stage of the forest sites sampled, and there was no difference in the number of individuals in the soil of the four forest sites. Mean nematode abundance in soil in banana plantations was about twice as high compared to the banana-palmito mixed stands and to the forest sites.